Permuting Contractual Autonomy: An Ontological Inquiry into Green Clauses and Environmental Custodianship in Uzbekistan - Toqsanbaeva Ayjamal (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
This scholarly undertaking meticulously dissects the burgeoning integration of esoteric ecological exigencies into the lex mercatoria, focusing on "green clauses" within commercial contracts in Uzbekistan's evolving legal firmament. It addresses a lacuna in jurisprudence regarding their precise ontological delineation and consistent pragmatic instantiation. The investigation illuminates their jural genesis, explicates their practical implementation, and proffers concrete recommendations for efficacy. A cardinal revelation posits that these clauses inherently permute contractual autonomy to subsume ecumenical environmental custodianship. The research's pertinence is underscored by recent Uzbek legislative promulgations, notably the Law on Limiting Greenhouse Gas Emissions, which introduces "carbon units" and "carbon footprint," thus laying a foundational legal bedrock for market-based environmental instrumentalities. This work contributes to a robust legal architecture for sustainable development, recalibrating Uzbekistan's commercial sector within global ecological paradigms.